Prevalence and pathology of Newcastle disease in broiler at Bochaganj Upazila of Dinajpur, Bangladesh (Asian Journal of Medical and Biological Research, 2016)
The study was schemed to investigate the prevalence, pathological conditions, mortality and clinical features of Newcastle disease in the small scale commercial broiler farms at Bochaganj upazila of Dinajpur district during January to June, 2014. A total 1950 birds (from 5 farms), among which 160 diseased and dead birds were selected out of which 99 (5.35%) birds were found to be positive for Newcastle disease. The clinical signs of the affected birds were sneezing, coughing, nasal discharge, laboured breathing, and torticolis. Broiler were inactive, weak and rough in appearance, greenish watery diarrhoea occur severely. Nervous sign include clonic, spasm and paralysis of the legs and wings. In this observation, the gross pathological lesions were slight to severe haemorrhages in caecal tonsils, typical lesions were proventricular haemorrhage, most commonly seen in the surface near the junction with the proventriculus. The prevalence of Newcastle disease in Bochaganj upazila was 5.35%. Mortality of Newcastle disease in non-vaccinated and vaccinated broiler flock was 20.76% and 4.6%, respectively.Asian J. Med. Biol. Res. June 2016, 2(2): 352-356